Sliding mode control for speed loop combined with MTPA strategy of IPMSM applied in electric vehicles - Thi Hoai Thu Anh, An; Hung Cuong, Tran; Minh Chien, Duong (Bulletin of Electrical Engineering and Informatics, 2025)
The interior permanent magnet synchronous motor (IPMSM) 's outstanding features, such as quick torque mobility capability, broad speed adjustability, robust mechanical structure, and high efficiency, make it particularly suitable for electric vehicle propulsion systems. This paper proposes a speed loop utilising the sliding mode control (SMC) with exponential reaching law and proportional-derivative term-ks, facilitating quicker transient responses and enhancing system stability. Moreover, coupling with the maximum torque per ampere strategy (MTPA) on current to improve motor torque in flux weakening region and to extend the adjustable range of motor speed for electric vehicle propulsion systems is discussed. Furthermore, with the proposed control methods and strategies, the system achieves stability despite environmental noise and uncertainties caused by uncertain parameters. Finally, simulation results conducted on MATLAB/Simulink software verify the correctness of the proposed control methods.